Uninscribed Amethyst Scarabs from the Southern Levant - David, Arlette (Bulletin of ASOR, 2019)
Prompted by the discovery of a schematic uninscribed amethyst scarab at Tel Abel Beth Maacah in the Upper Galilee, an overview of such scarabs found in the southern Levant is provided, with a typological analysis and a tentative dating and origin of these pieces.